Soil Monitoring System Using LoRa-Based ANN Method For Rice Plant Growth - Rokhmat Albasyih; Amang Sudarsono; Norma Ningsih (International Journal Labs, 2023)
Farmers only use approximation, the application of this approximation can cause the quality of the soil in rice fields to be infertile. In this research, an agricultural land monitoring system was created using an agricultural land monitoring tool to make it easier for farmers to monitor the land to get good crop yields. The test results obtained are data collected on the land according to the parameters needed from rice plants. The research design was made in the form of a monitoring tool which will later display on the website to make it easier for farmers to check the land to be planted with rice remotely. This system also uses the Artificial Neural Network method which functions to predict soil conditions. The result of this system is to make it easier for farmers to get agricultural land that meets the criteria for quality rice plant